The influence of the STAD learning model towards improving mathematics learning outcomes - Nina Rostiana; Dinn Wahyudin (Himpunan Pengembang Kurikulum Indonesia, 2025)
Mathematics is still a difficult and tedious subject for elementary school students, which leads to low learning outcomes. Many factors influence students' mathematics learning outcomes. Analyzing the influence of the Student Teams Achievement Division (STAD) learning model on the mathematics learning outcomes of grade 5 elementary school students is the aim of this research. This study adopted a quasi-experimental design by comparing two unequal groups of students. Data is collected through various methods, including tests and observations. Data analysis was carried out statistically to test research hypotheses and determine the effectiveness of a particular treatment. There is a very statistically significant difference between the experimental and control groups' average post-test scores. These results support the hypothesis that the STAD learning model effectively increases learning achievement. Apart from that, cooperative learning in STAD can increase student interaction, learning motivation, and a deeper understanding of mathematical concepts. The implications of this research indicate that STAD can be an alternative learning strategy teachers implement to improve student learning outcomes. Abstrak Pelajaran matematika masih menjadi pelajaran sulit dan menjenuhkan bagi peserta didik SD, yang berujung pada hasil belajar rendah. Banyak faktor memengaruhi hasil belajar matematika peserta didik. Menganalisis pengaruh model pembelajaran Student Teams Achievement Division (STAD) terhadap hasil belajar matematika peserta didik kelas 5 SD adalah tujuan penelitian ini. Penelitian ini mengadopsi desain kuasi-eksperimental dengan membandingkan dua kelompok peserta didik yang tidak setara. Data dikumpulkan melalui berbagai metode, termasuk tes dan observasi. Analisis data dilakukan secara statistik untuk menguji hipotesis penelitian guna mengetahui efektivitas suatu perlakuan tertentu. Terdapat perbedaan sangat signifikan secara statistik antara rata-rata nilai post-test kelompok eksperimen dan kelompok kontrol. Hasil ini mendukung hipotesis bahwa model pembelajaran STAD efektif meningkatkan prestasi belajar. Selain itu, pembelajaran kooperatif dalam STAD mampu meningkatkan interaksi antar peserta didik, motivasi belajar, serta pemahaman konsep matematika secara lebih mendalam. Implikasi penelitian ini menunjukkan bahwa STAD dapat menjadi alternatif strategi pembelajaran yang diterapkan guru untuk meningkatkan hasil belajar peserta didik. Kata Kunci: hasil belajar; matematika peserta didik SD; STAD